The socio-cultural component in Sustainable Regeneration of the Military Heritage sites; a case study of Rafael Hoyos Rubio Fort in Rimac, from the perspective of its local actors - Balarezo Alberca, Giovanna María (2020)
Historic military properties in the city of Lima have been experiencing changes in recent years due to the improvised growth of the city, resulting in the gradual loss of the functions and activities for which they were projected. The limited use of military infrastructure has contributed to the inescapable interest of the private sector for real estate development as these are considerable land extensions immersed in the urban fabric. These changes have been developed without prior analysis of their importance and heritage value for the city and its residents. The present investigation analyzes the case of Rafael Hoyos Rubio Fort in the district of Rímac to understand urban regeneration of these military heritage sites, reflected from the social and cultural perspectives. In the way, the study aims to identify the strengths and weaknesses of these urban en- claves to formulate short, medium and long term goals for their possible integration into the city, to promote the interaction of local government with citizens in order to recognize their needs, and what would empower the citizen for their active participation in the processes of change.